Preparation, characterization, and evaluation of polymeric resin (BHMET) from the reaction of malic anhydride with recycled PET as a corrosion inhibitor for Csteel in HCl - A, Yasir; A, Khalaf; M, Khalaf (Innovaciencia, 2019)
Introduction: The plastic soft drink bottle from polyethylene terephthalate (PET) was introduced to consumers in 1970s. Because PET have ester group its chemical recycling is preferred. To control and reduce the environmental pollution recycling and reusing of PET has turned into an imperative procedure from the ecological perspective and it has given business opportunity because of far reaching use and accessibility of PET polymer. Also another source of pollution to the environment was the corrosion of materials. Corrosion is the deterioration and loss of a material and its critical properties due to chemical, electrochemical and other reactions of the exposed material surface with the surrounding environment. Understanding corrosion mechanisms allow to use corrosion-resistant materials and altering designs. Organic inhibitors are very efficient to protect the metals from corrosion in all chemicals (acidic, basic and salt) media. There were many types of corrosion inhibitors and the organic inhibitor are being applied widely to protect metals from corrosion in many aggressive media. The aim of this study is to utilize waste PET-bottles will be depolarized by 2,2-dithioethanol to produce (Bis(2-((2-hydroxyethyl) thio) ethyl) terephthalate (BHTE), then by reacting of (BHTE) with maleic anhydride to produce Bis (2-((6-Mono malic acid –hydroxyethyl ester) sulfanyl) ethyl terephthalate(BHMET). The prepared (BHMET) will be used as corrosion inhibitor and its efficiency to protect the carbon steel in acidic will be assessed. Materials and Methods: Depolymerization of PET waste done with 2,2-dithioethanol. The weight proportion of PET to 2,2-dithioethanol 1:8 (wt%) and zinc acetate (0.5 wt% based on PET) was added as catalyst. Temperature of the reaction mixture was between 160-180 oC for 12 h, then the reaction mixture was kept at 140 oC for 3 h, then allowed to cool to room temperature. With vigorous agitation distilled water in excess to the reaction mixture to allow the black liquid viscous compound oligomer of Bis(2-((2-hydroxyethyl) thio) ethyl terephthalate (BHET) to precipitate. In a three neck round bottom (250 ml) attached with mechanical stirrer and thermometer (5.7gm) of (BHET) compound was added and heated for (15 min.) at (60 OC). Then (2.5gm) of malic anhydride and (1%) sulfuric acid was added. By the mechanical stirrer the mixture was mixed for (50 min.) at temperature (80OC). After the reaction the mixture was washed with distilled water to avoid the acid residue. Scheme (1) shows the mechanism for the prepared (BHMET) corrosion inhibitor.